Improving the Students’ Vocabulary through Short Story of Eight Grade Students MTs. Nurul Falah Kefamenanu - Siahaan, Desta Gloria; Bria, Maria Jeni Josefa; Kamlasi, Imanuel (ICONELT, 2022)
This research was to obtain the improvement of students’ vocabulary through short story as learning media for students at MTs. Nurul Falah Kefamenanu. This research used classroom action research (CAR). It has been conducted in to 2 cycles. Each cycle consisted of four steps: planning, action, observation and reflecting. The technique of this research used test of short story that consists of multiple choice, essay and questionnaire. The test consisted of cycle I and cycle II. The researchers analysed the average score of each test obtain the improvement of students’ vocabulary by using short story. The result of research showed that Short Story significantly improved the students’ vocabulary. It can be seen in the result of the students’ average score in the Cycle I was 64,81 and in the Cycle II was 70. It can be concluded that short story as one of the techniques to improve the students’ vocabulary.